Test Some New Media for Cultivation of Gram Positive and Gram Negative Bacteria - Firas Nabeeh Jaafar1 , Wala’a Shawkat Ali2 , Nadia Kamil Bashar1 , Rayim Sabah Abbood1 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Possibility of using the wastes of used paper to prepare a culture medium for bacterial growth was carriedout in this study, five experimental culture media (paper waste extract agar, glucose paper waste extract agar,yeast extract paper waste extract agar, NaCl paper waste extract agar and GYN paper waste extract agar)that made from the extract of used papers were prepared to cultivation two species of Gram positive bacteria(Staphylococcus aureus and Streptococcus spp.) and two species of Gram negative bacteria (Escherichiacoli and Pseudomonas aeruginosa) in comparison with readymade media (nutrient agar and brain-heartinfusion agar). Heavy growth of bacteria was appeared on yeast extract paper waste extract agar and GYNpaper waste extract agar media, while no growth was happen on the other three experimental culture media.The results of statistical analysis found that there is no significant different at P?0.05, using LSD test amongyeast extract paper waste extract agar , GYN paper waste extract agar and nutrient agar or brain-heartinfusion agar media .These results indicate likelihood of using two experimental culture media instead ofnutrient agar or brain-heart infusion agar to cultivation of bacteria.